1978
DOI: 10.1093/nar/5.7.2525
|View full text |Cite
|
Sign up to set email alerts
|

Reverse transcriptase: a monitor for perturbation effects of spin labels covalently bound to nucleic acids

Abstract: The sensitive biological assay for reverse transcriptase was used to monitor potential perturbation effects of spin labels covalently bound to various nucleic acids or nucleic acid analogs to the extent of about one label per 100 residues. The inhibitory properties of the spin labeled and unlabeled biopolymers were compared for evaluating possible interference of the reporter group in protein-nucleic acid interaction studies. The amount of inhibitor required for 50% inhibition (ED50) was determined for the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1980
1980
1982
1982

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…At a es4U:U ratio of 1:33, no enhanced inhibition by (es4U:U)n is observed, and the spin labels are relatively far apart (on the average) and unable to form complexes coordinated with Zn2+ at two sites. This observation is consistent with earlier studies concerning the inhibition of RNA-dependent DNA polymerase by various spin-labeled nucleic acids obtained by alternative routes, which showed that the spin label had virtually no effect on the inhibitory properties of these nucleic acids as evidenced by the kinetic patterns of inhibition and ED5o (gg/ml required for 50% inhibition of enzyme activity) values of labeled vs. unlabeled species (20). As the ratio of es4U:U is increased to 1:16 or 1:8, the probability of complexing two nitroxide radicals with Zn2+ is increased, and enhanced inhibition by (eS4UU)n is observed.…”
Section: Discussionsupporting
confidence: 92%
“…At a es4U:U ratio of 1:33, no enhanced inhibition by (es4U:U)n is observed, and the spin labels are relatively far apart (on the average) and unable to form complexes coordinated with Zn2+ at two sites. This observation is consistent with earlier studies concerning the inhibition of RNA-dependent DNA polymerase by various spin-labeled nucleic acids obtained by alternative routes, which showed that the spin label had virtually no effect on the inhibitory properties of these nucleic acids as evidenced by the kinetic patterns of inhibition and ED5o (gg/ml required for 50% inhibition of enzyme activity) values of labeled vs. unlabeled species (20). As the ratio of es4U:U is increased to 1:16 or 1:8, the probability of complexing two nitroxide radicals with Zn2+ is increased, and enhanced inhibition by (eS4UU)n is observed.…”
Section: Discussionsupporting
confidence: 92%